A review on dependence graph in social reasoning mechanism - Lau, Billy; Singh, Ashutosh Kumar; Tan, Terence Peng Lian (Kluwer, 2015)
Dependence between heterogeneous agents has gained attention from researchers because dependence influences the capabilities of a particular agent in a multi-agent system. In this paper, we have reviewed and discussed the dependence graph which is also known as interdependence graph in some author’s work. Dependence graph is originally proposed in the social reasoning mechanism to visualize the dependence network. In this paper, dependence network is explained and an in depth analysis of the dependence graph is presented as well. Next, we are going to discuss about the social phenomena and group formation of the dependence graph. In addition, the further works of other authors are listed in this paper. Also, we discuss the drawbacks and propose some potential solution for enhancing the dependence graph.